Conducting rapid research to aid the design of a health systems governance intervention in the Somali Region of Ethiopia - Pieterse, Pieternella (Frontiers in Sociology, 2022)
Introduction The rapid research described in this chapter was conducted as an assignment for a UN agency in Ethiopia's Somali Region. The agency's aim was support the implementation of an interim citizen engagement intervention, with a view of supporting of the Ethiopian Government's Citizen Score Card at primary healthcare facilities and hospitals in future. Many health facilities in Somali Region struggle with budget shortages related to ineffective budget planning and budget execution at woreda health office levels. In this context, an intervention to first improve budget accountability, through the implementation of citizen audits, was proposed. Methodology The rapid study focused on five woredas (districts) within Somali Region, where interviews were conducted with the heads of woreda health offices. In the same five woredas, directors of healthcare facilities were interviewed and offices and healthcare facilities were observed. The framework of assessment and analysis was based on health systems literature on fragile and conflict affected states guided the questions for the health authorities and health facility management. Findings The research yielded five distinct mini case studies covering woreda health office planning and budgeting capacity and support (or lack thereof), and related impressions of challenges regarding healthcare delivery at health facilities in the same five woredas. Results The findings demonstrated that the capacity for healthcare planning and budgeting Somali Region at woreda level varied significantly and that little guidance was available from regional level health authorities. Frontline health services clearly suffered from budget shortages as a result. Conclusion The research provided an evidence base for the delay of the roll-out of the Community Scorecard implementation across Somali Region. In a context whereby health facilities remain under-resourced due to budgeting constraints, a citizen-service provider-focused accountability intervention would have been of limited utility. The rapid case study research, conducted by condensing the usual case study research process, allowed for the production of evidence that was “robust enough” to demonstrate heterogeneity and challenges regarding budgeting quality across the five research sites. This evidence clearly transcended the hitherto anecdotal evidence that woreda-level health budget planning remains an area that faces significant shortcomings.